Application of ultrasound imaging to subject-specific modelling of the human musculoskeletal system - Passmore, Elyse; Lai, Adrian; Sangeux, Morgan; Schache, Anthony G.; Pandy, Marcus G. (Meccanica (Milan), 2017)
Ultrasound imaging is relatively inexpensive, does not involve ionising radiation, and requires much shorter scan times compared with other imaging modalities such as magnetic resonance imaging and computed tomography. These advantages make it an appealing option in both clinical and research settings. Computational models of the human musculoskeletal system are used for a wide range of applications in biomechanics, from studies of muscle function during locomotion to pre-operative planning of orthopaedic surgeries. The integration of ultrasound imaging with musculoskeletal modelling has the potential to create new opportunities in the study of human movement science. Subject-specific measures of muscle–tendon properties and bone geometry obtained from ultrasound imaging are now being used in conjunction with detailed models of the musculoskeletal system to better understand muscle–tendon function during normal and pathological movement. This approach also allows more rigorous validation studies to be performed to quantify the accuracy of musculoskeletal modelling predictions. We have been using ultrasound imaging to create subject-specific models of the human musculoskeletal system for the purpose of simulating normal and pathological gait. This review describes our experiences in using ultrasound imaging to measure muscle–tendon architecture and bone geometry in vivo. Recent studies focused on integrating ultrasound imaging and musculoskeletal modelling to determine muscle–tendon function in human walking and running are also described.